2015
DOI: 10.4028/www.scientific.net/amr.1134.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Black Structures towards Heat Build-Up Measurements and its Dynamic Properties

Abstract: The aim of this study is to investigate the effect of different carbon black structures towards heat build-up measurements and its dynamic properties such as tangent delta, loss modulus and storage modulus on the industrial rubber compounds containing Natural Rubber (NR) and Styrene Butadiene Rubber (SBR). Different carbon black structures were used and characterised with respect to their rheological and physical properties. Heat Build-up test is a testing procedure which is used to measure the rate of heat ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…The addition of carbon black increased storage modulus at low strain dynamic (Figure 3(a) and (b)), which indicated the effect of filler network, higher carbon black contents and higher storage modulus. The extent of the reinforcing effect is also increased when a larger amount of carbon black is incorporated, 15,16 because the binding force between the carbon black and rubber molecules prohibited the movement of the polymer chain. 22 We found that a graph of Δ E ( E max E min ) as a function of carbon black content is linear (see the inserted graph in the Figure 3(a) and (b)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of carbon black increased storage modulus at low strain dynamic (Figure 3(a) and (b)), which indicated the effect of filler network, higher carbon black contents and higher storage modulus. The extent of the reinforcing effect is also increased when a larger amount of carbon black is incorporated, 15,16 because the binding force between the carbon black and rubber molecules prohibited the movement of the polymer chain. 22 We found that a graph of Δ E ( E max E min ) as a function of carbon black content is linear (see the inserted graph in the Figure 3(a) and (b)).…”
Section: Resultsmentioning
confidence: 99%
“…Compared at the same ratio, they presented higher tensile strength but undesirable higher heat buildup. [11][12][13][14][15] Increasing the surface area and including surface treatment gave higher abrasion resistance, chemical adsorption or reaction, modulus (at elongation over 300%) and also heat build-up.…”
Section: Introductionmentioning
confidence: 99%
“…The key objective of compounding is concerned with securing an optimum balance between the three significant characteristics, namely cost, processability and final vulcanizate properties. The established ingredients of tyre tread consist of synthetic rubbers [ 62 ], petroleum-based fillers [ 63 ] performance modifiers [ 64 ], processing aids, [ 65 ] etc. The majority of the ingredients are synthetic materials with non-environmentally friendly backgrounds and output characteristics.…”
Section: Green Tyres Industry: An Overviewmentioning
confidence: 99%
“…Depletion of fossil fuel sources also forced us to find alternatives for CB since it is produced by the partial combustion of crude oil. Rizuan and co-workers have investigated the effect of carbon black structures in heat build-up and dynamic properties of NR and SBR [ 63 ]. The incorporation of low and high black structures in NR/SBR exhibits lower heat generation which results in lower damping value and low rolling resistance.…”
Section: Green Tyres Industry: An Overviewmentioning
confidence: 99%
“…Tipe karet alam yang paling dominan digunakan dalam pembuatan ban kendaraan adalah SIR 20, sedangkan dari golongan karet sintetik adalah styrene butadiene rubber (SBR) dan polybutadiene rubber (BR). Karet alam dikenal memiliki sifat kalor timbul yang rendah (Rizuan et al, 2016). Sementara karet SBR dan BR diketahui memiliki keunggulan ketahanan abrasi yang sangat baik (Sae-oui et al, 2017).…”
Section: Abstrak Abstractunclassified